Bridging the gap: does a specialist eating disorder service, aimed at developing a continuum of community care, make a difference?. (August 2013) - Newton, John; Bosanac, Peter; Mancuso, Sam; Castle, David
Objective: In 2010, the authors identified in a separate publication, Mind the evidence gap, the sparse evidence-base for the treatment of adult anorexia nervosa and barriers to accessing care. We report on the ensuing development, implementation and first 18-month results of a novel eating disorder service bridging the primary and specialist continuum of care in Victoria, Australia. Method: Using literature review, stakeholder, and consumer and carer consultation, a model for a community eating disorder service was developed and then implemented. All patients entering the service were then assessed at intake and, if they gave consent, at 12 month follow-up. Results: From December 2010 to July 2012, 208 patients accessed The Body Image Eating Disorders Treatment and Recovery Service (BETRS). Fifty-three per cent had a diagnosis of anorexia nervosa and the mean number of co-morbid psychiatric diagnoses was two. Twenty-three per cent attended a day patient programme and showed a significant improvement in their body mass index. Measures of depression, anxiety and eating disorder symptomatology showed a concomitant, significant decrease. Conclusions: The development of BETRS has led to markedly improved access and effectiveness of specialist services in the region.